New Stereo Vision Digital Camera System for Simultaneous Measurement of Cloud Base Height and Atmospheric Visibility - Janeiro, Fernando M. (2014)
Clouds play an important role in many aspects of everyday life. They affect both the local weather as well as the global climate and are an important parameter on climate change studies. Cloud parameters are also important for weather prediction models which make use of actual measurements. It is thus important to have low-cost instrumentation that can be deployed in the field to measure those parameters. This kind of instruments should also be automated and robust since they may be deployed in remote places and be subject to adverse weather conditions. Although clouds are very important in environmental systems, they are also an essential component of airplane safety when visual flight rules (VFR) are enforced, such as in most small aerodromes where it is not economically viable to install instruments for assisted flying. Under VFR there are strict limits on the height of the cloud base, cloud cover and atmospheric visibility that ensure the safety of the pilots and planes. Although there are instruments, available in the market, to measure those parameters, their relatively high cost makes them unavailable in many local aerodromes. In this work we present a new prototype which has been recently developed and deployed in a local aerodrome as proof of concept. It is composed by two digital cameras that capture photographs of the sky and allow the measurement of the cloud height from the parallax effect. The new developments consist on having a new geometry which allows the simultaneous measurement of cloud base height, wind speed at cloud base height and atmospheric visibility, which was not previously possible with only two cameras. The new orientation of the cameras comes at the cost of a more complex geometry to measure the cloud base height. The atmospheric visibility is calculated from the Lambert-Beer law after the measurement of the contrast between a set of dark objects and the background sky. The prototype includes the latest hardware developments that allow its cost to remain low even with its increased functionality. Also, a new control software was also developed to ensure that the two cameras are triggered simultaneously. This is a major requirement that affects the final uncertainty of the measurements due to the constant movement of the clouds in the sky. Since accurate orientation of the cameras can be a very demanding task in field deployments, an automated calibration procedure has been developed, that removes the need for an accurate alignment. It consists on photographing the stars, which do not exhibit parallax due to the long distances involved, and deducing the inherent misalignments of the two cameras. The known misalignments are then used to correct the cloud photos. These developments will be described in the detail, along with an uncertainty analysis of the measurement setup. Measurements of cloud base height and atmospheric visibility will be presented and compared with measurements from other in-situ instruments.